Characteristics of Citations Used by Humanities Researchers - Zainab, A.N.; Goi, S.S. (1997)
Analysis of 5,610 citations from 104 master's degree and doctoral dissertations submitted to the University of Malaya between 1984 and 1994 in the humanities (religion and philosophy; history; language and literature) has been conducted. The average citation per dissertation in various humanities fields, are 56.7 for religion and philosophy; 102 for history and 45.3 for language and literature. Over 52% (2,927) of the citations were to books, 23.55% (1,321) to journal articles, 9.43% (529) to book chapters and 6.24% (350) to theses. A total of 4,766 (89.94%) authors of the citations were single authors and 700 authors formed the core authors contributing a total of 2,160 (36.59%) of total citations. The use by humanities researchers of a wider number of journals and book titles indicate that they need to use a greater number of sources for their research information needs. More than 50% of the citations aged between 1 to 20 years and some more than 100 years. Researchers use a high percentage of documents in the English language even though about 66% of the dissertations were written in the Malay language. The references by and large are of Malaysian or Asian in origin reflecting resource needs of these researchers.